المنهج الظاهراتي وتطبيقاته في الدراسات السوسيولوجية - بونيف، حنان; بوساق، هجيرة Bousaq, Hajirah (مؤسسة كنوز الحكمة للنشر والتوزيع, 2023)
يهدف هذا المقال إلى التعريف بالمنهج الظاهراتي ومجمل مبادئه وأهم تطبيقاته في الدراسات السوسيولوجية والذي يمثل أحد المناهج الكيفية التي يمكن للباحثين في مجال علم الاجتماع الاستفادة منها في إعداد الدراسات والبحوث العلمية، وتطوير البحوث السوسيولوجية بشكل عام والسوسيوتربوية بشكل خاص، من خلال تقديم للظاهراتية عند الرواد بدءا من مؤسسها "إدموند هوسرل" والتعريف بالمنهج الظاهراتي وأهم مبادئه، اختيار العينات واختيار المشاركين، كذلك أدوات جمع البيانات وطرق تخزينها وكذلك عرض وتحديد معانيها، مع عرض موجز لمجمل الفروقات بين المنهج الظاهراتي وغيره من المناهج الكيفية الأخرى. من بين النتائج المتوصل إليها: أهمية المنهج الظاهراتي بشكل خاص والمناهج الكيفية بشكل عام، ضرورة فهم الباحثين في علم اجتماع لهذا المنهج وتطبيقه من أجل الزيادة في الكفاءة والوصول إلى المعاني الجوهرية عن المواضيع المدروسة. This article aims to introduce the phenomenological approach, its principles, and its most important applications in sociological studies. It is considered as one of the most approaches that researchers can use it in their studies through introducing phenomenology its pioneers, starting with its founder, Edmund Husserl, and defining the phenomenological approach and its most important principles, Selection of samples and selection of participants as well data collection tools and it's methods of storing, as well as presenting and defining their meanings, with a brief presentation of the overall differences between the phenomenological approach and other qualitative approaches. Among the results reached: the importance of the phenomenological approach in particular and the qualitative approaches in general, the need for researchers in sociology to understand and apply this approach in order to increase the efficiency and reach the essential meanings of the topics studied.
Keywords: علم الاجتماع -- الظواهر السوسيولوجية -- العقل البشري -- الذات الإنسانية